A Transformative Paradigm for Relational Nursing: A Narrative Review of the Theory of Communion-in-Caring - CYRUZ P. TUPPAL; Leah Kalayaan A. Pellacœur; Shanine Mae P. Tuppal; Yu Dan; Arif Adi Setiawan; Bradley K. Loo; Jennifer Joy R. Olivar; Manal Al Zadjali; Said Nasser Al Harthy (Caring: Indonesian Journal of Nursing Science, 2025)
Modern nursing faces increasing challenges, including depersonalization, burnout, and the fragmentation of care delivery. In response, the Theory of Communion-in-Caring provides a transformative framework that re-centers nursing on its relational, moral, and spiritual dimensions. The objective of this review is to critically examine the theory’s conceptual, methodological, and practical contributions to nursing science. A qualitative content review was conducted on the first edition of the book, focusing on its philosophical assumptions, theoretical foundations, methodological proposals, practical applications, and future directions. Thematic analysis guided the data organization, using conceptual clarity, methodological rigor, contextual relevance, and interdisciplinary potential as key evaluative criteria. The review highlighted the theory’s grounding in Filipino cultural values and global relational ethics, positioning caring as a sacred communion of mutual presence and transformation. The theory promotes methodological pluralism, including phenomenology, narrative inquiry, and mixed methods that align with its relational ontology. It offers concrete strategies for nursing education, clinical practice, and administration, with promising interdisciplinary and community-based applications. Despite challenges in measurement and implementation, the theory presents a culturally authentic and philosophically coherent model of care. In conclusion, the Theory of Communion-in-Caring makes a timely contribution by restoring dignity, empathy, and relational meaning in nursing, offering a valuable paradigm for both local and global healthcare contexts. Keywords: Nursing Theory, Caring Science, Communion, Filipino Values, Relational Ethics